Manajemen Jaringan Internet Menggunakan Mikrotik Router di SMA Negeri 2 Bojonegoro - Sakur (Jurnal Pendidikan Madrasah, 2022)
The use of information and communication technology in the world of education is unavoidable. The use of networks to access computers remotely and connect them to the internet is increasingly needed by teachers and students to obtain learning information. The network system used must be well managed, especially in managing internet bandwidth so that the connection of each computer has access to the internet evenly and maximally as needed. SMA Negeri 2 Bojonegoro in its teaching and learning activities has utilized information and communication technology, especially has utilized computer networks and the internet as a medium for data and information communication. However, the computer and internet network systems at SMA Negeri 2 Bojonegoro have not been managed properly. The solution to improve the effectiveness of using and managing internet bandwidth at SMA Negeri 2 Bojonegoro is to design and implement network management with Mikrotik Router to make it easier for administrators to manage the network. This research uses the Network Development Life Cycle (NDLC) method as a method of developing computer network management at SMA Negeri 2 Bojonegoro. The results showed that the use of a network system using a Mikrotik router in managing internet bandwidth efficiently facilitates and facilitates various activities related to internet use.